Listeria monocytogenes–Associated Acute Cholecystitis: A Case Report and Review of the Literature - Christine Kim; Robert Seby; Mahmoud Khreis; Catherine Derber (Annals of Internal Medicine: Clinical Cases)
People who are pregnant, immunocompromised, or elderly are at risk for listeriosis, a life-threatening condition. Although Listeria monocytogenes may be asymptomatic or limited to uncomplicated gastroenteritis in healthy adults, it can cause invasive disease such as meningitis and bacteremia in susceptible individuals. Less commonly, L monocytogenes can cause a focal site of infection such as acute cholecystitis. In the literature, previous cases of L monocytogenes–associated acute cholecystitis were treated with antibiotics either provided or held and a cholecystectomy. We present an 80-year-old man who recovered from acute cholecystitis due to L monocytogenes with appropriate antibiotic coverage and a percutaneous cholecystostomy.